2019
DOI: 10.1038/s41598-019-45158-3
|View full text |Cite
|
Sign up to set email alerts
|

Redox balance, metabolic fingerprint and physiological characterization in contrasting North East Indian rice for Aluminum stress tolerance

Abstract: Aluminum (Al) toxicity is a serious problem for rice crop productivity in acidic soils worldwide. The present work was conducted to look out for the alteration in ROS homeostasis; metabolic fingerprint; and morphology in two contrasting Indica rice cultivars of North East India (NE India) to Al toxicity. Al stress led to excess accumulation of ROS (H 2 O 2 and O 2 − ), and this in turn induced ROS mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 92 publications
(119 reference statements)
2
27
0
Order By: Relevance
“…We marked an enhanced GPX expression upon induction of stress which is in the line reported in several higher plant species [2]. Further SOD-mediated catalyses for dismutation reaction detoxify the cellular upset [3,5]. Our study is in the path of similar finding reported above.…”
Section: Discussionsupporting
confidence: 89%
“…We marked an enhanced GPX expression upon induction of stress which is in the line reported in several higher plant species [2]. Further SOD-mediated catalyses for dismutation reaction detoxify the cellular upset [3,5]. Our study is in the path of similar finding reported above.…”
Section: Discussionsupporting
confidence: 89%
“…Although most studies have pointed to the suppression of TCA cycle activity, the protective role of TCA cycle metabolites under oxidative stress conditions has been also discussed. For example, the role of malate in the induction of protective antioxidant defense was demonstrated in green algae Scenedesmus obliquus and banana fruits [ 97 , 98 ], and citrate presence in the exudate of aluminum-tolerant Indica rice cultivars was shown to contribute to the tolerance of aluminum-induced oxidative stress [ 99 ].…”
Section: Metabolic Signature Of Oxidative Stress In Plantsmentioning
confidence: 99%
“…Proline, a general stress response metabolite associated with chloroplasts and photosynthesis [ 8 ], was reported to decrease in Arabidopsis cell culture treated with H 2 O 2 [ 24 ], but increased in roots experiencing oxidative stress [ 25 , 28 ]. Oxidative stress resulting from aluminum toxicity was accompanied by a significant increase in proline in aluminum-tolerant rice cultivars [ 99 ]. The accumulation of proline under oxidative stress conditions and its role in the maintenance of redox balance have been demonstrated, although the ROS-scavenging ability of proline is still debated [ 117 , 118 ].…”
Section: Metabolic Signature Of Oxidative Stress In Plantsmentioning
confidence: 99%
See 2 more Smart Citations